Analisa Kerusakan Cooling System Engine C 6.4 Caterpillar - Abdul Halik; faisyal Faisyal; Hidayat Hidayat; Baso Cante (Politeknik Negeri Samarinda, 2021)
The cooling system is one of five systems in the engine, which function to maintain a stable engine operating temperature. This research was conducted to determine the damage to the cooling system components. The object under investigation is the water pump and thermostart on the Caterpillar C6.4 engine. The method used in this research is field observation, library research, measuring, inspection, and consulting with experts. According to the appropriate literature, component damage that commonly occurs in water pumps and thermostarts is erosion, cavitation erosion, abrasive wear, adhesive wear, and fretting corrosion. After a visual inspection is carried out, measurements are carried out, then an analysis is carried out referring to the appropriate literature, in this case the GRPTS and SIS. The results of this study found that there was corrosion damage to components due to improper maintenance and the use of coolant that was not up to standard.